Late Pleistocene dust dynamics and pedogenesis in Southern Eurasia – Detailed insights from the loess profile Toshan (NE Iran). (15th January 2018) - Vlaminck, Stefan; Kehl, Martin; Rolf, Christian; Franz, Sven Oliver; Lauer, Tobias; Lehndorff, Eva; Frechen, Manfred; Khormali, Farhad
Abstract: In southern Eurasia recurrent phases of aridization, dust source extension and enhanced Aeolian sedimentation alternated with moister intervals, promoting reduced deflation areas and dust accumulation in the context of late Pleistocene climate changes. Weathering and soil forming intensity in this greater region are, hence, mainly governed by fluctuations in the balance between dust supply and moisture availability. Among the hitherto known sections, the Toshan loess-soil sequence (LPS) represents a key site due to the quality of the record and the multitude of available data giving detailed insights into the timing and magnitude of dust accumulation and soil formation of the region. To elucidate these dynamics for much of the past 130.000 years bulk mineralogical and geochemical data are presented supplemented by a high resolution magnetic susceptibility record and by the results of a detailed micromorphological study of loess at Toshan. The last interglacial Luvisol/Phaeozem-like (∼MIS 5e) and the early glacial interstadial steppic palaeosols (∼MIS 5 c and a) are characterized by gradually increasing grain-size and decreasing degrees in decomposition of micaceous and mafic minerals. Pronounced feldspar weathering is detected in the last interglacial and modern soils only, which formed under reduced or absent dust deposition on penultimate and last glacial loess, respectively (postsedimentary). The overall pedosedimentary conditions correspond to large scale trends of increasing drought, dust accumulation and wind strength in southern Eurasia in relation to decreasing moisture availability towards the early Pleniglacial (∼MIS 4), causing soil formation under ongoing dust deposition (synsedimentary). Similar intervals of synsedimentary soil formation are recorded during the interglacial/interstadial-stadial transitions of the early glacial and during pleniglacial (∼MIS 4 to 2) interstadials. The latter are marked by gradual increases in magnetic susceptibility, colour and decreasing texture. Conversely, silicate weathering could not be detected, suggesting that grain-size fluctuations are a primary feature. Thus, windy and arid pleniglacial conditions in southern Eurasia were interrupted by intermittent phases of synsedimentary soil formation, in response to short-lived and relatively moist interstadials. Although the interrelation of these incipient soils, throughout southern Eurasia is afflicted with considerable restrictions, the oscillatory pattern of the Toshan LPS bears great similarity with millennial-scale oscillations recorded in limnic archives of western Asia. Highlights: Clear distinction between syn- and postsedimentary palaeosol formation. Detailed study of weathering intensity. 130.000 years of dust dynamics and pedogenesis in high-resolution. Supraregional correlation of results. Interpretations are based on high quality data.